Teachers as Catalysts for Shaping Religious Character in Youth - Azhari , Imam; Astutik, Anita Puji (Indonesian Journal of Islamic Studies, 2024)
General Background: The youth are pivotal for national development and are increasingly required to navigate the complexities of a technologically advanced world. Specific Background: Despite this necessity, many young individuals are ill-prepared for technological engagement and often misuse these tools, which adversely affects their character. Character education is critical and must be integrated into both formal and non-formal educational systems. Knowledge Gap: While the role of Islamic boarding schools in character education is acknowledged, the specific contributions of teachers within this context remain underexplored. Aims: This research aims to elucidate the role of teachers in fostering a generation of religious professionals at the Wali Barokah Islamic Boarding School in Kediri, East Java. Results: Employing a qualitative descriptive approach, data were collected through observations, interviews, and documentation, revealing that teachers serve as facilitators, motivators, and role models. Findings indicated that teachers received a high observation score of 91%, highlighting their effectiveness in character formation. Novelty: This study provides a comprehensive examination of how teacher involvement directly influences the development of religious character among students, emphasizing the multifaceted role teachers play in Islamic education. Implications: The results underscore the necessity for enhanced teacher training and support to strengthen character education in Islamic boarding schools, thereby equipping the next generation with the moral framework needed to successfully navigate contemporary challenges and contribute positively to society. Highlights: Importance of character education in Islamic boarding schools for youth. Teachers significantly shape students' religious character as role models. Qualitative research reveals effective teaching methods impacting student development. Keywords: Islamic education, character formation, teachers' role, qualitative research, religious professionals